L'interaction entre un dispositif d'apprentissage numérique et les représentations de l'apprenant - Cécile Dejoux; Fiammetta Cascioli (Centre National d'Enseignement à Distance, 2018)
MOOC can be considered nowadays a training modality in company beside other traditional ones. This research aims at studying the performativity of MOOC on the professional daily life of participants. An exploratory research has been carried on in collaboration with Safran Group's Corporate University on a sample of 10 participants. Questionnaires have been conducted and associated with semi-exploratory interviews. Results show that the MOOC's theoretical elements have had a performativity impact on the cognitive manipulations participants realize on their managerial representations.